Analisis Reaksi Pasar Modal Atas Pengumuman Kenaikan BI Rate Tanggal 12 November 2013 - Dwi Cahyaningdyah; Nidya Arum Cahyasani (Jurnal Maksipreneur, 2017)
The purpose of this study was to analyze differences in the market reaction, as measured by abnormal returns and trading volume activity in the period before and after the announcement of the increase in the BI Rate. This study uses event study research design, observation period were 10 days before and 10 days after the event. The populations in this study were all members of LQ45 companies. The study sample was taken by purposive sampling technique. The method of data collection is the documentation. The variables of this study are the abnormal return and trading volume activity. The analysis used in this study is different test paired sample t-test. Based on the research results, the stock market reaction test showed no significant difference between the average abnormal return before and after the announcement of the increase in the BI Rate. While testing the reaction by using the average trading volume activity indicators showed a significant difference between the periods before and after the announcement of the increase in the BI Rate.